2017
DOI: 10.1002/cjoc.201600723
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Carbonates from Alkenyl and Alkynyl Substrates

Abstract: As an extensively used chemical product, cyclic carbonate was generally synthesized by transesterification, or the cycloaddition of epoxides, diols with CO2. To reduce the production costs and expand the raw materials, alkenyl and alkynyl substrates have caused much attention in the synthesis of cyclic carbonates, such as olefins, allyl alcohols and propargylic alcohols. Based on the alkenyl substrate, the synthetic process involves a continuous reaction of oxidative carboxylation, with epoxide or halohydrin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 99 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…All the reactions showed >99% production of regioisomer A, which indicated that the steric hindrance of these secondary amines is favourable to the regioselective ring-opening of DPMOD. Compared with 4-methylpiperidine (12), the use of 13 caused lower conversion of DPMOD (72%), while 12 led to a 100% conversion of DPMOD. It is reasonable that the methyl group of 12 was more electron-donating than the hydroxyl group of 13 and thus improved the reactivity of 12 towards DPMOD.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…All the reactions showed >99% production of regioisomer A, which indicated that the steric hindrance of these secondary amines is favourable to the regioselective ring-opening of DPMOD. Compared with 4-methylpiperidine (12), the use of 13 caused lower conversion of DPMOD (72%), while 12 led to a 100% conversion of DPMOD. It is reasonable that the methyl group of 12 was more electron-donating than the hydroxyl group of 13 and thus improved the reactivity of 12 towards DPMOD.…”
Section: Methodsmentioning
confidence: 92%
“…[7,8] As an inert C1 compound, CO 2 is usually converted to the five-membered cyclic carbonate via the coupling reaction with alkyne derivatives or epoxides that are high-energy compounds. [9][10][11][12] Followed by ring-opening addition reaction with amines, these cyclic carbonates can be effectively converted to the urethane compounds. This reaction is the basic chemistry of the non-isocyanate route for making polyurethanes (PUs).…”
Section: Introductionmentioning
confidence: 99%
“…A wide spectrum of compounds have been studied as catalysts for this synthesis, both homogeneous and heterogeneous, as well as immobilized ones, such as onium quaternary salts [3][4][5][6], metal complexes [7][8][9][10], metal-organic frameworks [11,12], and ionic liquids [13][14][15][16][17]. However, the direct synthesis of cyclic carbonates from CO 2 and olefin as raw materials is of growing interest [18,19]. This process, i.e., an oxidative carboxylation of olefins with CO 2 , proceeds in two stages.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the immobilization of homogeneous catalysts on the surface of organic or inorganic supports are of particular interest. Examples of the use of immobilized catalysts in the direct synthesis of cyclic carbonates can be found in the literature [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of one-carbon (C1) compounds such as carbon dioxide (CO 2 ) to make polymers has drawn much attention in the past few decades. [1][2][3][4][5][6][7][8][9][10][11][12][13] As a sulfur analogue of CO 2 , carbon sulfide (COS) is a by-product in the process of burning fossil fuels or coal gas, or the corruption of livings. It causes acid rain, ozonosphere damage [14] and haze [15] by a series of photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%